Dynamic loop gain increases upon adopting the supine body position during sleep in patients with obstructive sleep apnoea - Joosten, Simon A. (Respirology, 2017)
BACKGROUND AND OBJECTIVE: Obstructive sleep apnoea (OSA) is typically worse in the supine versus lateral sleeping position. One potential factor driving this observation is a fall in lung volume in the supine position which is expected by theory to increase a key OSA pathogenic factor: dynamic ventilatory control instability [i.e. loop gain]. We aimed to quantify dynamic loop gain in OSA patients in the lateral and supine positions, and to explore the relationship between change in dynamic loop gain and change in lung volume with position. METHODS: Data from 20 patients enrolled in previous studies on the effect of body position on OSA pathogenesis was retrospectively analysed. Dynamic loop gain was calculated from routinely collected polysomnographic signals using a previously validated mathematical model. Lung volumes were measured in the awake state with a nitrogen washout technique. RESULTS: Dynamic loop gain was significantly higher in the supine than in the lateral position (0.77±0.15 vs 0.68±0.14, P=0.012). Supine functional residual capacity (FRC) was significantly lower than lateral FRC (81.0±15.4 vs 87.3±18.4% of the seated FRC, P=0.021). The reduced FRC we observed on moving to the supine position was predicted by theory to increase loop gain by 10.2 (0.6, 17.1)%, a value similar to the observed increase of 8.4 (−1.5, 31.0)%. CONCLUSION: Dynamic loop gain increased by a small but statistically significant amount when moving from the lateral to supine position and this may, in part, contribute to the worsening of OSA in the supine sleeping position.